First record of “Bigeye trevally” Caranx sexfasciatus Quoy & Gaimard 1825 (Carangiformes: Carangidae) from Peru - Campos-León, Sarita; Miranda-Romero, Junior; Moreno, Andrey; Ramírez, Jorge L.; Siccha-Ramirez, Zoila Raquel (Zootaxa, 2025)
Specimens of Caranx sexfasciatus (Bigeye trevally) were collected from northern and central Peru between 2021 and 2023, marking the first confirmed record of this species in Peruvian waters. This study represents a significant extension of its known range, previously reported only as far south as Ecuador. Morphological and molecular analyses were conducted to confirm species identification, revealing diagnostic coloration and physical traits. Observations near oil platforms suggest artificial reefs play a critical role in its habitat preference. The species’ presence in the Humboldt Current may be linked to the El Niño-Southern Oscillation (ENSO), which elevates sea temperatures and influences marine biodiversity distribution. This report not only extends the known range of C. sexfasciatus but also highlights the ecological importance of artificial reefs and climate events in shaping its distribution.